ADIPOSE-DERIVED STEM CELLS (ADSCS) PRETREATED WITH VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) PROMOTED WOUND HEALING IN RAT SKIN BURN MODEL - FARYAD, Q; FAZAL, N; IJAZ, B; BILAL, AZ; MALIK, K; LATIEF, N (Biological and Clinical Sciences Research Journal, 2022)
Stem cells are extensively used for regenerative purposes as they are unspecialized cells capable of renewal and differentiation. Growth factors like vascular endothelial growth factor (VEGF) play a crucial role in enhancing the regenerative potential of stem cells. The present study was designed to elucidate the effects of VEGF preconditioning in accelerating the regenerative potential of adipose-derived stem cells (ADSCs) for wound healing. In vivo study was carried out using female Sprague Dawley (SD) rats randomly divided into three groups, i.e., VEGF preconditioned ADSCs transplanted group (Pre-Tx), normal ADSCs transplanted group (N-Tx) and control group. ADCS were isolated from female SD rats and treated with VEGF for the Pre-Tx group. At 21st day post-transplantation, the wound in the Pre-Tx group was completely closed. However, the wound was not fully healed in the N-Tx group and the Control group. For further analysis, the experimental area of skin tissues was taken from all groups and examined histologically. The cellularity and granulation were thicker in the pre-Tx group and thicker in the pre-Tx group and thicker, indicating rapid wound recovery. Furthermore, the polymerase chain reaction results also confirmed the down-regulation of apoptotic marker caspase3, which indicates less cell death at the injury site and up-regulation of certain growth factors like IGF, sdf1α and some other markers like E cadherin and vimentin. RT-PCR analysis revealed significant up-regulation of all these factors in the pre-Tx group compared to other groups. These results suggest that VEGF pre-conditioning improves the reparative potency of ADSCs by increasing their survival rate and stimulating the secretion of various growth factors having crucial involvement in angiogenesis and recovery of damaged tissue.